Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) Terhadap Kompetensi Belajar Siswa Ranah Kognitif - Betaria Putra (Departement of Mathematics Education, 2021)
The research aims to determine the effect of cooperative learning type Student Teams Achievement Division (STAD) toward students’ learning cognitive competence. The design of the research was semi experimental research that used the static group comparison design. The population of this research were all of nineth-grade students in SMA Negeri 1 Kerinci. The sample was taken by using purposive sampling technique. The instrument of this research was objective test or multiple choise to get students’ learning cognitive competence data. Based on the t- test, the research showed that students’ learning cognitive competence who learning by using STAD was better than students’ learning cognitive competence in control group.